Mechanism of action of antiplatelet drugs on decompression sickness in rats: A protective effect of anti-GPIIbIIIa therapy - Lambrechts, K.; Pontier, J.; Mazur, A.; Theron, M.; Buzzacott, Peter; Wang, Q.; Belhomme, M.; Guerrero, F. (2015)
Copyright © 2015 the American Physiological Society. Literature highlights the involvement of disseminated thrombosis in the pathophysiology of decompression sickness (DCS). We examined the effect of several antithrombotic treatments targeting various pathways on DCS outcome: acetyl salicylate, prasugrel, abciximab, and enoxaparin. Rats were randomly assigned to six groups. Groups 1 and 2 were a control nondiving group (C; n = 10) and a control diving group (CD; n = 30). Animals in Groups 3 to 6 were treated before hyperbaric exposure (HBE) with either prasugrel (n = 10), acetyl salicylate (n = 10), enoxaparin (n = 10), or abciximab (n = 10). Blood samples were taken for platelet factor 4 (PF4), thiobarbituric acid reactive substances (TBARS), and von Willebrand factor analysis. Onset of DCS symptoms and death were recorded during a 60-min observation period after HBE. Although we observed fewer outcomes of DCS in all treated groups compared with the CD, statistical significance was reached in abciximab only (20% vs. 73%, respectively, P = 0.007). We also observed significantly higher levels of plasmatic PF4 in abciximab (8.14 ± 1.40 ng/ml; P = 0.004) and enoxaparin groups (8.01 ± 0.80 ng/ml; P = 0.021) compared with the C group (6.45 ± 1.90 ng/ml) but not CD group (8.14 ± 1.40 ng/ml). Plasmatic levels of TBARS were significantly higher in the CD group than the C group (49.04 ± 11.20 µM vs. 34.44 ± 5.70 µM, P = 0.002). This effect was prevented by all treatments. Our results suggest that abciximab pre-treatment, a powerful glycoprotein IIb/IIIa receptor antagonist, has a strong protective effect on decompression risk by significantly improving DCS outcome. Besides its powerful inhibitory action on platelet aggregation, we suggest that abciximab could also act through its effects on vascular function, oxidative stress, and/or inflammation.